2020
DOI: 10.1093/ckj/sfaa194
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil:lymphocyte ratio predicts short-term outcome of COVID-19 in haemodialysis patients

Abstract: Background Information regarding coronavirus disease 2019 (COVID-19) in haemodialysis (HD) patients is limited and early studies suggest a poor outcome. We aimed to identify clinical and biological markers associated with severe forms of COVID-19 in HD patients. Methods We conducted a prospective, observational and multicentric study. Sixty-two consecutive adult HD patients with confirmed COVID-19 from four dialysis facilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 22 publications
(26 reference statements)
4
12
0
1
Order By: Relevance
“…Out of all these ratios, in our study, NLR and LCR were associated with the severe form and mortality. Very similar observer data by Qin et al [ 26 ] showed that an NLR >5.2 was associated with the most severe form of COVID-19 within a cohort of 452 patients, while Mutinelli-Szymanski et al [ 15 ], in a prospective, observational, and multicentric study of 62 adult HD patients, observed that an NLR >3.7 at day 7 was associated with the severe form and with poor survival. Therefore, we believe that NLR and LCR could be helpful for clinicians to identify patients who may develop a severe form of the disease at an early stage.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Out of all these ratios, in our study, NLR and LCR were associated with the severe form and mortality. Very similar observer data by Qin et al [ 26 ] showed that an NLR >5.2 was associated with the most severe form of COVID-19 within a cohort of 452 patients, while Mutinelli-Szymanski et al [ 15 ], in a prospective, observational, and multicentric study of 62 adult HD patients, observed that an NLR >3.7 at day 7 was associated with the severe form and with poor survival. Therefore, we believe that NLR and LCR could be helpful for clinicians to identify patients who may develop a severe form of the disease at an early stage.…”
Section: Discussionsupporting
confidence: 56%
“…However, the NLR, PLR, MLR, and LCR are biomarkers of systemic inflammation, available in almost all laboratories, and are rarely used in this infection. The first of them has been the most thoroughly studied and has shown prognostic ability in multiple clinical settings, such as acute kidney injury [ 27 ], kidney disease [ 28 ], cardiovascular disease [ 29 ], ANCA-associated vasculitis [ 30 ], cancer patients [ 31 ], renal transplantation [ 32 ], and recently COVID-19 as a short-term predictor marker associated with severe forms of COVID-19 in HD patients [ 15 , 18 , 33 ]. In our study, the CRP levels at diagnosis were almost double in patients who died, as compared to survivors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms such as fever, asthenia, cough and dyspnea were more frequent in the severe group, consistent with the results of a previous study performed on dialysis patients. 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, laboratory indices associated with worse COVID-19 prognosis included d-dimer, LDH, CRP, thrombocytopenia, lymphopenia and liver dysfunction. 8 , 9 , 10 , 11 Another study found that the N:L ratio was the major marker associated with severe forms and predicted short-term COVID-19 outcomes in hemodialysis patients. 9 …”
Section: Discussionmentioning
confidence: 99%